2022
DOI: 10.1371/journal.pone.0263794
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing SARS-CoV-2 from antigen tests

Abstract: Genomic surveillance empowers agile responses to SARS-CoV-2 by enabling scientists and public health analysts to issue recommendations aimed at slowing transmission, prioritizing contact tracing, and building a robust genomic sequencing surveillance strategy. Since the start of the pandemic, real time RT-PCR diagnostic testing from upper respiratory specimens, such as nasopharyngeal (NP) swabs, has been the standard. Moreover, respiratory samples in viral transport media are the ideal specimen for SARS-CoV-2 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Our work highlights the importance of also monitoring N antigen diversity, to assess how new mutations may limit the performance of antigen tests. Finally, it was recently shown that SARS-CoV-2 genome sequencing from antigen tests is possible 43 . If this were to become a widely used surveillance tool, our study suggests that sequencing positive and negative antigen samples would be the optimal surveillance strategy to accurately detect both concordant and discordant variants.…”
Section: Discussionmentioning
confidence: 99%
“…Our work highlights the importance of also monitoring N antigen diversity, to assess how new mutations may limit the performance of antigen tests. Finally, it was recently shown that SARS-CoV-2 genome sequencing from antigen tests is possible 43 . If this were to become a widely used surveillance tool, our study suggests that sequencing positive and negative antigen samples would be the optimal surveillance strategy to accurately detect both concordant and discordant variants.…”
Section: Discussionmentioning
confidence: 99%
“…Our work highlights the importance of also monitoring N antigen diversity, to assess how new mutations may limit the performance of antigen tests. Finally, it was recently shown that SARS-CoV-2 genome sequencing from antigen tests is possible 41 . If this were to become a widely used surveillance tool, we estimate that sequencing positive and negative ANCOV samples would be the optimal surveillance strategy to accurately detect both concordant and discordant variants.…”
Section: Discussionmentioning
confidence: 99%
“…While a reflexive PCR test after a positive Ag-RDT diagnosis is currently performed to obtain samples suitable for sequencing (and is possible in many tertiary facilities in LMICs), this presents additional cost and logistical barriers. Recent studies showed that SARS-CoV-2 sequencing can be performed using materials obtained from Ag-RDTs performed at point-of-care [33][34][35] . Importantly, whole genomes can be recovered up to eight days after testing, providing opportunities for sequencing to be performed on samples performed through selftesting as well 33 .…”
Section: Discussionmentioning
confidence: 99%